Опыт и проблемы развития профессионального сетевого сообщества в средней школе - Уразакова, Г.Г. (My University, 2016)
In this article presented the experience of developing schooling professional unity across the school introduction the process of searching lessons in couching and mentoring.
Keywords: networkofteachers; evaluation; schooldevelopmentplan